Taking Action: A Cross-Modal Investigation of Discourse-Level Representations - Kaiser, Elsi (Frontiers in Psychology, 2012)
Segmenting stimuli into events and understanding the relations between those events is crucial for understanding the world. For example, on the linguistic level, successful language use requires the ability to recognize semantic coherence relations between events (e.g. causality, similarity). However, relatively little is known about the mental representation of discourse structure. We report two experiments that used a cross-modal priming paradigm to investigate how humans represent the relations between events. Participants repeated a motor action modeled by the experimenter (e.g. rolled a ball towards mini bowling pins to knock them over), and then completed an unrelated sentence-continuation task (e.g. provided a continuation for “Peter scratched John. …”). In two experiments, we tested whether and how the coherence relations represented by the motor actions (e.g., causal events vs. non-causal events) influence participants’ performance in the linguistic task. Our analyses focused on the coherence relations between the prompt sentences and participants’ continuations, as well as the referential shifts in the continuations. As a whole, the results suggest that the mental representations activated by motor actions overlap with the mental representations used during linguistic discourse-level processing, but nevertheless contain fine-grained information about sub-types of causality (reaction vs. consequence). In addition, the findings point to parallels between shifting one’s attention from one event to another and shifting one’s attention from one referent to another, and indicate that the event structure of causal sequences is conceptualized more like single events than like two distinct events. As a whole, the results point towards common representations activated by motor sequences and discourse-semantic relations, and further our understanding of the mental representation of discourse structure, an area that is still not yet well-understood.